Health‐Literacy‐Sensitive Diabetes Self‐Management Interventions: A Systematic Review and Meta‐Analysis. Issue 4 (22nd April 2016) - Kim, Su Hyun; Lee, Anna
ABSTRACT: Background: Low health literacy is a potential barrier to self‐management among patients with diabetes. A variety of strategies for low health literacy have been proposed for diabetes self‐management interventions, but interventions accommodating low health literacy have been heterogeneous in terms of content and have produced mixed results. Aim: To systematically review health‐literacy‐sensitive diabetes management interventions, with a focus on identifying strategies for accommodating patients with low health literacy, and to examine the efficacy of these interventions to improve health outcomes. Methods: PubMed, CINAHL, and EMBASE were searched for intervention studies published between January 2000 and January 2015. Two authors separately identified full‐texts according to the inclusion criteria and assessed study quality using the quantitative components of the Mixed Methods Appraisal Tool. The final list of studies to be analyzed was made through discussion. The meta‐analysis was conducted using a random effects model. Results: Thirteen studies were selected from the 490 studies found in our initial search. We identified a range of strategies for accommodating those with low health literacy in diabetes self‐management interventions, which encompassed four domains: written communication, spoken communication, empowerment, and language/cultural consideration. Using at least one of the spoken communication strategies led to positive cognitive/psychological, self‐care, and health outcomes. We found that, overall, health‐literacy‐sensitive diabetes management interventions were effective in reducing HbA1C level in the meta‐analysis. Linking Evidence to Action: Healthcare providers should consider active implementation of strategies for accommodating people with low health literacy in diabetes self‐management interventions. The routine use of spoken communication strategies would be necessary to achieve the best health outcomes in diabetes self‐management interventions. More research is needed to determine the individual effects of the key strategies that improve health and reduce health disparity.